2006
DOI: 10.1093/hmg/ddl247
|View full text |Cite
|
Sign up to set email alerts
|

5′ and 3′ region variability in the dopamine transporter gene ( SLC6A3 ), pesticide exposure and Parkinson's disease risk: a hypothesis-generating study

Abstract: The dopamine transporter gene (SLC6A3) is a candidate gene for Parkinson's disease (PD) on the basis of its critical role in dopaminergic neurotransmission. Previously, we identified 22 SNPs in the 5' region of SLC6A3, which segregate as eight haplotypes that differ in transcriptional activity when transfected in rat dopamine-producing cells. In the present work from a case-control study size of 293 cases and 395 controls, we employed a cladistic approach to examine gene-disease association. First, we found st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 78 publications
(70 reference statements)
4
41
0
Order By: Relevance
“…Interactions of paraoxonase and dopamine transporter genes and pesticides and PD also await replication. 29,30 To date, only an interaction of CYP2D6 gene polymorphisms and pesticides on the risk of PD has been independently replicated. 31,32 Information regarding specific subtypes of pesticides (e.g., by indication for use or by chemical class) and their association with PD is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions of paraoxonase and dopamine transporter genes and pesticides and PD also await replication. 29,30 To date, only an interaction of CYP2D6 gene polymorphisms and pesticides on the risk of PD has been independently replicated. 31,32 Information regarding specific subtypes of pesticides (e.g., by indication for use or by chemical class) and their association with PD is limited.…”
Section: Resultsmentioning
confidence: 99%
“…There are no conclusive results yet for the effect of the DAT VNTR as a risk factor for Parkinson disease. However, Kelada et al identified a haplotype corresponding with the T-A-9R haplotype that had a tendency of being a risk factor instead of a protective factor for Parkinson disease, though this was not significant (36). It remains difficult to understand the exact mechanisms of DAT expression, genotype, and the role of DAT in pathology, but the differences in DAT genotype and expression between healthy subjects and those who have disease might offer explanation of the crucial changes that reflect the pathologic mechanisms in disease.…”
Section: Discussionmentioning
confidence: 98%
“…It is also shown to interact with its transcription factor NR4A2 in conferring risk for smoking (322). In addition, epigenetic and environmental involvement further complicates statistical evaluation of genetic associations with ADHD and Parkinson’s disease (298, 323, 324). …”
Section: The Transporter Genes As Risk Factorsmentioning
confidence: 99%